PENGEMBANGAN KOMPETENSI GURU SEKOLAH DASAR MELALUI PENELITIAN TINDAKAN KELAS - Meilina Bustari (Fakultas Ilmu Pendidikan UNY, 2009)
A good education needs professional teachers. Professional teachers needs professional development programs. A professional development program that can be done by teachers is doing Classroom Action Research. Classroom action research is a practical research by teachers in class for improving instructional quality through planning, implementing, observing. and reflecting activities. All activities in classroom action research will improve teacher competencies. Successful implementation of classroom action research needs support and facilitation from school staffs especially the principal. Keywords: Improve teachercmpetencies, classroom action research.